Formation of distinctive nanostructured metastable polymorphs mediated by kinetic transition pathways in germanium - Mei Li; Xuqiang Liu; Sheng Jiang; Jesse S. Smith; Lihua Wang; Shang Peng; Yongjin Chen; Yu Gong; Chuanlong Lin; Wenge Yang; Ho-Kwang Mao (Matter and Radiation at Extremes)
High-pressure β-Sn germanium may transform into diverse metastable allotropes with distinctive nanostructures and unique physical properties via multiple pathways under decompression. However, the mechanism and transition kinetics remain poorly understood. Here, we investigate the formation of metastable phases and nanostructures in germanium via controllable transition pathways of β-Sn Ge under rapid decompression at different rates. High-resolution transmission electron microscopy reveals three distinct metastable phases with the distinctive nanostructures: an almost perfect st12 Ge crystal, nanosized bc8/r8 structures with amorphous boundaries, and amorphous Ge with nanosized clusters (0.8–2.5 nm). Fast in situ x-ray diffraction and x-ray absorption measurements indicate that these nanostructured products form in certain pressure regions via distinct kinetic pathways and are strongly correlated with nucleation rates and electronic transitions mediated by compression rate, temperature, and stress. This work provides deep insight into the controllable synthesis of metastable materials with unique crystal symmetries and nanostructures for potential applications.